Endometriosis and ART outcome: a retrospective analysis - S., Janani; Shankar, Kundavi; V., Geetha; Basith, Abdul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Endometriosis affects up to 30-40% of women seeking fertility treatment and is known to reduce fecundity. There remains a debate on the effect of endometriosis on the IVF outcome, with live birth not reported in most studies. This study looks at the impact of endometriosis on live birth rates after IVF and compares the chances of success with those without endometriosis. Methods: Retrospective analysis of women who underwent IVF at our institution for 2 years were included. Multiple factor infertility, ovulation disorders and donor program were excluded. The outcomes were compared for 4 cohorts - women with endometriosis, male factor infertility, tubal factor infertility and unexplained infertility. The primary outcome was live birth rate. Other outcome measures were total dose of gonadotropins used, mean number of oocytes collected, M2 oocyte rate, fertilization rate, implantation rate, and clinical pregnancy rate. Results: Patients diagnosed with endometriosis had lower mean number of oocytes collected (6.86 vs 7.69, 7.94, 7.45) and lower mean number of M2 oocytes (5.31 vs 6.21, 6.44, 5.91) but was not statistically significant. Endometriosis patients required significantly higher dose of gonadotropins when compared to controls (5365.79 IU; p-0.001). The per ET implantation rate (10.4% vs 17.8%, 22.5%, 19.2%), clinical pregnancy rate (8% vs 15%, 20%, 17%), live birth rate (7.92% vs 16.6%, 15.14%, 12%) and the cumulative live birth rate (27.9% vs 46.5%, 60%, 46.7%) were significantly less in women with endometriosis (p-0.039, p-0.021, p-0.001, p-0.039 respectively) and the effect is more pronounced with increasing disease severity. Conclusions: Endometriosis affects all aspects of IVF outcomes including folliculogenesis, embryo development and implantation. Though ovarian factor can be overruled by increasing the stimulation doses as in our study, methods to improve the implantation rates should be thought about in future.